2022
DOI: 10.3389/fpsyt.2022.919176
|View full text |Cite
|
Sign up to set email alerts
|

Association between sleep disturbance and mental health of healthcare workers: A systematic review and meta-analysis

Abstract: ObjectivesSleep disturbance and mental health are challenges for healthcare workers (HCWs). Especially during the COVID-19 pandemic, they experienced more severe sleep and mental health problems. However, the association between sleep disturbance and the mental health of HCWs is still controversial. This study aimed to systematically review the relationship by conducting a systematic review and meta-analysis.MethodTwo researchers retrieved the literature from Web of Science, PubMed, EMBASE, CINAHL, Psyclnfo, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 87 publications
2
6
0
Order By: Relevance
“…Similar findings were reported by Dong, Zhang, Zhu, and Lv (2020). Other studies have shown similar findings, with systematic reviews and meta-analyses showing even lower SD (Liu et al, 2022). The high prevalence of SD among nurses is due to work shifts and it seems that globally there is a lack of a system of proper shift distribution to ensure nurses a smooth circadian rhythm and avoid additional mental and physical strain resulting from poor sleep quality (Slavish et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Similar findings were reported by Dong, Zhang, Zhu, and Lv (2020). Other studies have shown similar findings, with systematic reviews and meta-analyses showing even lower SD (Liu et al, 2022). The high prevalence of SD among nurses is due to work shifts and it seems that globally there is a lack of a system of proper shift distribution to ensure nurses a smooth circadian rhythm and avoid additional mental and physical strain resulting from poor sleep quality (Slavish et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Shift work increases the risk of cardiovascular and digestive system disorders, sleep disturbances, neuropsychiatric disorders, and chronic pain, and is related to a higher incidence of accidents at work and lower work satisfaction among employees. In the context of paramedics undertaking shift work, there is a limited number of health consequences documented [19][20][21][22][23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Some of those factors are related to their mental health, as the correlation between sleep and mental health has been shown in recent years [ 21 , 22 ]. The positive correlation between sleep disturbances and mental health problems was confirmed by a systematic review and meta-analysis of studies involving healthcare workers conducted during the COVID-19 pandemic [ 23 ]. Nonetheless, it is relevant to note that, according to that systematic review [ 23 ], some conditions faced by healthcare workers during the COVID-19 pandemic, such as exposition to the disease, the possible transmission of infection to family members, shortage of personal protective equipment, extended working hours, and decisions about allocating limited resources to patients, also presented a risk of adverse mental health.…”
Section: Introductionmentioning
confidence: 90%
“…The positive correlation between sleep disturbances and mental health problems was confirmed by a systematic review and meta-analysis of studies involving healthcare workers conducted during the COVID-19 pandemic [ 23 ]. Nonetheless, it is relevant to note that, according to that systematic review [ 23 ], some conditions faced by healthcare workers during the COVID-19 pandemic, such as exposition to the disease, the possible transmission of infection to family members, shortage of personal protective equipment, extended working hours, and decisions about allocating limited resources to patients, also presented a risk of adverse mental health. Although definitive conclusions regarding bidirectionality cannot be made for most sleep disturbances, the best available evidence suggests that some of the disturbances, such as insomnia, are bidirectionally related to mental health problems such as anxiety and depression [ 24 ].…”
Section: Introductionmentioning
confidence: 90%